Assessment of muscular strength of knee flexors and extensors in individuals with and without osteoarthritis - Sebastião Iberes Lopes Melo; Juliane de Oliveira; Roberta Castilhos Detânico; Rudnei Palhano; Renata Marcelino Schwinden; Mário César de Andrade; João Otacílio Libardoni dos Santos (Universidade Federal de Santa Catarina, 2008)
The aim of this study was to evaluate concentric and eccentric torque in individuals with and without knee osteoarthritis, and who did and did not practice physical activity. Specifically: to compare concentric and eccentric torque between groups; to compare the torques of dominant and non-dominant limbs within groups; to compare the concentric hamstrings/quadriceps ratio between groups. Fifty-eight elderly people participated, 32 with knee osteoarthritis and 26 with healthy knees. An isokinetic KinCom dynamometer was used for data collection. Concentric and eccentric peak torques of the quadriceps and hamstrings, normalized for body weight and concentric peak torque hamstring/quadriceps ratio of both sides were the study variables. At the Biomechanics Laboratory the following procedures were carried out: 1) identification form; 2) anthropometry; 3) warm-up and stretching; 4) positioning of the individual in a seated position with knee flexion of 90º and the back supported; 5) familiarization with the equipment; 6) acquisition of three reciprocal maximal concentric and eccentric contractions at 60º/s. Descriptive statistics and the Wilcoxon and the U Mann-Whitney tests were used to analyze data, to p≤0.05. The majority of concentric and eccentric torques in the control group were higher than those in the knee osteoarthritis group, with the exception of the concentric torque of non-dominant hamstrings and the eccentric quadriceps ofthe non-dominant limb. Although not significant, dominance seems to be determinant of increased torques in individuals withoutknee osteoarthritis. No statistically significant differences were detected between those who did and those who did not take part in physical activity. The results demonstrate that osteoarthritis provokes decrease of force especially in quadriceps.